Quantitatively examining the interaction between cybercrime and physical crime - Doss, Daniel Adrian; Scherr, Daniel (Society Register, 2023)
This study examined the differences and relationships between reported incidents of cybercrime and physical crime within U.S. society nationally. The examined period encompassed the years between 2001 and 2020. The study outcomes showed that a relationship existed between reported incidents of cybercrime and reported incidents of physical crime (p = 0.00; α = 0.05). More specifically, it appeared that relationships existed between the reported incidents of cybercrime and the reported incidents of physical crimes representing robbery rate (p = 0.01; α = 0.05), burglary rate (p = 0.00; α = 0.05), and larceny theft rate (p = 0.00; α = 0.05). It also appeared that a difference (p = 0.00; α = 0.05) existed between reported incidents of cybercrime and physical crime, wherein greater quantities of physical crime were exhibited societally during the examined period.